2008
DOI: 10.1556/achrom.20.2008.3.10
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of an RP-HPLC method for simultaneous analysis of drotaverine and omeprazole in a tablet dosage form

Abstract: A simple, rapid reversed-phase high-performance liquid chromatographic method has been developed and validated for simultaneous estimation of drotaverine and omeprazole in a tablet dosage form. A C 18 column was used with a 60:40 (v/v) mixture of methanol and ammonium acetate (0.1 M, pH 5, adjusted with orthophosphoric acid) as mobile phase at a flow rate of 1.5 mL min −1 . UV detection was performed at 319 nm. The method was validated for accuracy, precision, linearity, specificity and sensitivity in accordan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…The chromatographic separation of drotaverine and omeprazole was achieved on a C 18 column with methanol and 0.1 m ammonium acetate pH 5, adjusted with orthophosphoric acid as the mobile phase in a ratio of 60:40 v/v. Drotaverine (log P 5.35) is ionized at acidic pH and the methanol in the mobile phase causes solvation of the ionized analyte drotaverine and is retained more in the column than the less nonpolar analyte omeprazole (log P 2.23 Panigrahi & Sharma, 2008).…”
Section: Influence Of Organic Modifier On Retentionmentioning
confidence: 99%
“…The chromatographic separation of drotaverine and omeprazole was achieved on a C 18 column with methanol and 0.1 m ammonium acetate pH 5, adjusted with orthophosphoric acid as the mobile phase in a ratio of 60:40 v/v. Drotaverine (log P 5.35) is ionized at acidic pH and the methanol in the mobile phase causes solvation of the ionized analyte drotaverine and is retained more in the column than the less nonpolar analyte omeprazole (log P 2.23 Panigrahi & Sharma, 2008).…”
Section: Influence Of Organic Modifier On Retentionmentioning
confidence: 99%
“…It is a NSAID; used in the management of osteoarthritis; rheumatoid arthritis; and ankylosing spondylitis [3] . A few UV spectrophotometric andHPLC [4][5][6][7] methods have been reported individually or in combination with other drugs for estimation of DRH. The aim of present study wasto propose a simple and sensitive method for quantification of DRHand AF to validate the procedures in order to demonstrate its good analytical and statistical parameters.…”
Section: Introductionmentioning
confidence: 99%
“…A detailed literature survey revealed that there are some analytical methods reported for the estimation of drotaverine either individually or in combination with other drugs like HPTLC [ 8 ], spectrophotometric [ 9 – 14 ], by derivative spectrophotometry [ 15 ], and by HPLC [ 16 – 32 ]. The route of synthesis of drotaverine and possible degradants resulted in four known impurities, Impurity 1, Impurity 2, Impurity 3, and Impurity 4, which are not reported in any of the pharmacopeia.…”
Section: Introductionmentioning
confidence: 99%